Characterization of MOSkin detector for in vivo dose verification during Cobalt-60 high dose-rate intracavitary brachytherapy. (February 2019) - Jamalludin, Zulaikha; Jong, Wei Loong; Abdul Malik, Rozita; Rosenfeld, Anatoly; Ung, Ngie Min
Highlights: MO Skin was characterized for HDR brachytherapy using Co-60. MO Skin possesses suitable physical characteristics for in vivo dosimetry. Linearity and reproducibility of MO Skin were excellent under Co-60 irradiation. Point dose deviations between TPS and MO Skin ranged from −9% to 5% Abstract: In vivo dosimetry in high dose-rate (HDR) intracavitary brachytherapy (ICBT) is important for assessing the true dose received by surrounding organs at risk during treatment. It also serves as part of the treatment delivery quality assurance and verification program with the use of a suitable dosimeter. Such a dosimeter should be characterized under brachytherapy conditions before clinical application to ensure the accuracy of in vivo measurement. In this study, a MOSFET-based detector, MO Skin, was calibrated and characterized under HDR Cobalt-60 (Co-60) brachytherapy source. MO Skin possessed the major advantages of having small physical and dosimetric sizes of 4.8 × 10 −6 mm 3 with the ability to provide real-time measurements. Using solid water and polymethyl methacrylate (PMMA) phantom, the detectors' reproducibility, linearity, angular and distance dependency was tested for its suitability as an in vivo detector. Correction factors to account for differences in depth measurements were determined. The MO Skin detector showed a reliable response when tested under Co-60 brachytherapy range of doses with an excellent linearity of R 2 = 0.9997 and acceptable reproducibility. A phantom verification study was also conducted to verify the differences between MO Skin responses and treatment planning (TPS) calculated doses. By taking into account several correction factors, deviations ranging between 0.01 and 0.4 Gy were found between MO Skin measured and TPS doses at measurement distance of 20–55 mm. The use of MO Skin as the dosimeter of choice for in vivo dosimetry under Co-60 brachytherapy condition is feasible.